Speaking Skills of Children Aged 4–5 Years at Pembina Agropolitan Kindergarten Kabila District Bone Bolango Regency - Tri Sela Lauding (Journal of Educational Technology and Innovation, 2026)
Speaking ability is an important aspect of early childhood language development, yet several children still experience difficulties in vocabulary use, sentence construction, and oral communication during learning activities. Previous studies mostly focused on improving speaking ability through instructional methods and media, while qualitative studies describing children’s actual speaking conditions remain limited. Therefore, this study aimed to describe the speaking ability of children aged 4–5 years at TK Pembina Agropolitan, Kabila District, Bone Bolango Regency. This study employed a descriptive qualitative approach involving six children as the main research subjects. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings showed that some children were able to use simple vocabulary, construct understandable sentences, answer questions appropriately, and express ideas confidently during classroom activities. However, several children still demonstrated limited vocabulary, incomplete sentence structures, hesitation in speaking, and low confidence during oral interaction. The discussion revealed that speaking ability develops through social interaction, language stimulation, and classroom communication experiences. These findings indicate that interactive learning activities and teacher support are important in improving children’s confidence and speaking development in early childhood education.